Writing an academic paper for publication - Simkhada, PP; van Teijlingen, E; Hundley, V (Health Renaissance, 2013)
Health Renaissance, January-April 2013; Vol. 11 No.1; 1-5 DOI: http://dx.doi.org/10.3126/hren.v11i1.7592